Critical Analysis of Various Works of the Kutubus Sittah Book: A Review of the Reliability, Consistency, and Relevance of the Hadiths - Muhammad Jamil; Engkos Kosasih; Muhammad Al Mighwar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The Bukuulus Sittah is a collection of hadiths that is highly respected in the Islamic tradition, but critical analysis of the reliability, consistency and relevance of the hadiths in it requires attention. This paper aims to present a critical analysis of various works of the Bukuulus Sittah with a focus on these three aspects. The analysis methodology involves tracing the original text of the Bukuulus Sittah and recent critical studies. The results of the analysis show complexity in the reliability, consistency and relevance of the hadiths, emphasizing the need for a critical and contextual approach in understanding and applying these hadiths.